Dada : art and anti-art - Richter, Hans (London : Thames and Hudson, 1978)
Where and how Dada began is almost as difficult to determine as Horner's birthplace, writes Hans Richter, who was associated with the movement from its early days. Here he records its history from its beginnings in wartime Zürich to its collapse in the Paris of the 1920s. By selecting passages from manifestos and other documents of the time Professor Richter recreates the events of those days. Dada had an inevitable place in the development of art, and the creative function of its planned outbursts can now be seen. Dada led on from Expressionism, Cubism and Futurism, and in turn prepared the way for Surrealism. It was enlivened by bizarre and extravagant personalities, notably Tristan Tzara, Francis Picabia, Hans Arp, Kurt Schwitters, Marcel Duchamp, Max Ernst and Man Ray, whose contributions are fully discussed. The spirit of Dada has reappeared, in the 1960s, in such movements as Pop Art, which are surveyed in the final section.
Arp, Hans (Jean) ; Baader, Johannes ; Baargeld, Johannes Theodor ; Ball, Hugo ; Boccioni, Umberto ; Breton, André ; Buffet-Picabia, Gabrielle ; Cendrars, Blaise ; Chamberlain, John ; Charchoune, Serge ; De Chirico, Giorgio ; Cocteau, Jean ; Cravan, Arthur ; Crotti, Jean ; van Doesburg, Theo ; Duchamp, Marcel ; Duchamp, Suzanne ; Eggeling, Viking ; Einstein, Carl ; Eluard, Paul ; Ernst, Max ; Grosz, George ; Hardekopf, Ferdinand ; Hausmann, Raoul ; Heartfield, John ; Hennings, Emmy ; Higgins, Edward ; Hoech, Hannah ; Huelsenbeck, Richard ; Huidobro, Vincente ; Janco, Marcel ; Jung, Franz ; Kaprow, Allan ; Kassak, Lajos ; Lichtenstein, Roy ; Man Ray ; Mehring, Walter ; Pagani, Enzo ; Pansaers, Clément ; Picabia, Francis ; Pougny, Jean ; Van Rees, Otto ; Ribémont-Dessaignes, Georges ; Richter, Hans ; Satie, Erik ; Savinio, Alberto ; Schad, Christian ; Schwitters, Kurt ; Serner, Walter ; Slodki, Marcel ; Soupault, Philippe ; Spoerri, Daniel ; Taeuber-Arp, Sophie ; Tzara, Tristan ; Vaché, Jacques
Appendix p. 223-228, bibliog. p. 229-237
Engels
boek